Novel ABCB4 mutation in a Chinese female patient with progressive familial intrahepatic cholestasis type 3: a case report - Zhenping Wu; Siying Zhang; Lunli Zhang; Ming Li (Diagnostic Pathology, 2020)
Abstract Background Progressive familial intrahepatic cholestasis (PFIC) is a rare group of autosomal recessive hereditary hepatic diseases. There are three types of PFIC, classified according to the mutated gene. For example, PFIC type 3 (PFIC3) is due to mutations in the ABCB4 gene (encoding multidrug-resistant protein 3 [MDR3]). Case presentation We present a 19-year-old Chinese female patient who had a 2-year history of recurrent liver dysfunction, with mainly elevated alkaline phosphatase and γ-glutamyl transpeptidase(γ-GT) levels. After excluding other causes of abnormal liver function and cholestasis, the final diagnosis of PFIC3 was confirmed by histopathological examination and gene detection. The immunohistochemical results showed no MDR3 protein expression in the bile duct membrane. Genetic sequencing analysis revealed a novel heterozygous 2137G > A; p. V713M mutation (Exon 17) and a synonymous 504C > T; p. N168N mutation (Exon 6) in ABCB4. Conclusions Our patient with long-term liver dysfunction demonstrated that elevated alkaline phosphatase and γ-GT levels should be associated with the diagnosis of PFIC3, and gene detection is the key to diagnosis. From our in silico analysis, the novel mutation p. V713M in Exon 17 was predicted to affect protein function, with a SIFT (Sorting Intolerant from Tolerant) score of 0.02, indicating a deleterious effect. Further studies are necessary to investigate the impact of the novel heterozygous 2137G > A; p. V713M mutation (Exon 17) on functional defects of MDR3 and PFIC3.